Serum amyloid A level correlated with endoscopic findings in patients with Crohn's disease—Possible biomarker for evaluating mucosal healing. Issue 6 (June 2018) - Ishihara, Shunji; Tada, Yasumasa; Kawashima, Kousaku; Kataoka, Masatoshi; Sonoyama, Hiroki; Yamashita, Noritsugu; Oka, Akihiko; Kusunoki, Ryusaku; Fukuba, Nobuhiko; Mishima, Yoshiyuki; Oshima, Naoki; Moriyama, Ichiro; et al.
Abstract: Background: Mucosal healing (MH) has been proposed as an essential therapeutic goal for treatment of Crohn's disease (CD) patients. The utility of serum amyloid A (SAA) for prediction of MH in CD patients is lacking. Aims: This study was conducted to evaluate the correlation of SAA with CD-related endoscopic disease activity. Methods: SAA levels in serum samples obtained from CD patients as well as endoscopic findings based on a simple endoscopic score for CD (SES-CD) were assessed in relation to CD activity index (CDAI). The diagnostic ability of MH in correlation with SAA level was evaluated using receiver operating characteristic (ROC) curve analysis. Results: Fifty-five patients with CD were enrolled. Mean SAA level was significantly higher in clinical and endoscopic active phases as compared to an inactive phase. SAA level was also significantly correlated with SES-CD (r = 0.64, p < 0.01) and CDAI (r = 0.42, p < 0.01). The area under the ROC curve for SAA level was 0.77 and the optimal cut-off value for SAA to predict MH was 5.9 μg/dl. SAA level was shown to be associated with MH, with a sensitivity of 68% and specificity of 83%. Conclusions: SAA may be a possible biomarker for evaluating MH in CD patients.